Pengembangan bahan ajar konsep pengantar bioteknologi untuk peserta didik fase E berbentuk e-handout - Khalida, Noor; Noorhidayati, Noorhidayati; Amintarti, Sri (Journal of Bio-Creaducation, 2024)
21st century learning demands creativity and innovation in the idea of digitizing teaching materials to facilitate students’ 6C competencies. The teaching material was chosen is E-handout. This study aims to describe the suitability, feasibility and readability of the results of the Development of Teaching Materials for Biotechnology Introduction Concepts for Phase E Students in the form of E-handout. This research uses the 4D model of Thiagarajan et al. (1974). The data collection technique uses validation instruments for suitability, feasibility and readability of students. The suitability and feasibility test subjects consisted of 3 validators. The readability test subjects consisted of 9 students of class XI-4 at SMAN 4 Banjarmasin T.A. 2023/2024. The results of research on the Development of Teaching Materials for Biotechnology Introduction Concepts for Phase E Students in the form of E-Handouts obtained: (1) The average suitability score of 4.62 which is classified as "very suitable" meaning that this E-Handout is very suitable for learning objectives, content, examples, language, format, and presentation. (2) The average feasibility score is 4.58 which is classified as "very feasible" meaning that this E-Handout is very feasible to use as teaching material in Biotechnology Introduction Concepts. (3) The average readability score is 4.59 which is classified as "very good" meaning this E-Handout is very good and easy to read. The result of research shows that the E-Handout has been developed can support learning of Biotechnology Introduction Concepts. Pembelajaran abad 21 menuntut kreativitas dan inovasi dalam ide digitalisasi bahan ajar untuk memfasilitasi kompetensi 6C peserta didik. Bahan ajar yang dipilih adalah E-Handout. Penelitian ini bertujuan untuk mendeskripsikan kesesuaian, kelayakan, dan keterbacaan hasil dari Pengembangan Bahan Ajar Konsep Pengantar Bioteknologi Untuk Peserta Didik Fase E (SMA) Berbentuk E-Handout. Penelitian ini menggunakan model 4D Thiagarajan et al. (1974). Teknik pengumpulan data menggunakan instrumen validasi kesesuaian, kelayakan, dan keterbacaan peserta didik. Subjek uji kesesuaian dan kelayakan terdiri atas 3 orang validator. Subjek uji keterbacaan terdiri dari 9 orang peserta didik kelas XI-4 SMAN 4 Banjarmasin T.A. 2023/2024. Hasil penelitian “Pengembangan Bahan Ajar Konsep Pengantar Bioteknologi Untuk Peserta Didik Fase E (SMA) Berbentuk E-Handout” memperoleh : (1) rata-rata skor kesesuaian sebesar 4,62 yang tergolong “sangat sesuai” artinya E-Handout ini telah sesuai dengan tujuan pembelajaran, isi, contoh-contoh, bahasa, format, dan penyajian. (2) Rata-rata skor kelayakan sebesar 4,58 yang tergolong “sangat layak” artinya E-Handout ini telah layak digunakan dalam pembelajaran. (3) Rata-rata skor keterbacaan sebesar 4,59 yang tergolong “sangat baik” artinya E-Handout ini sangat baik dan mudah dibaca oleh peserta didik. Hasil penelitian menunjukkan bahwa    E-Handout yang telah dikembangkan dapat menunjang pembelajaran konsep Pengantar Bioteknologi.